Ecosystems and human health : - Philp, Richard B. (Crc Press, 2014)
The book begins with the basic principles of pharmacology and toxicology, risk analysis, and air, water, and soil pollution. It then examines various toxicants and hazards, such as airborne hazards, halogenated hydrocarbons, metals, and organic solvents. Chapters also discuss food additives and contaminants, pesticides, hormone disrupters, radiation hazards, and natural environmental hazards such as venomous and toxic animals